Pharmacokinetics of tolfenamic acid after different administration routes in geese (Anser cygnoides) - Turk, Erdinc; Tekeli, Ibrahim Ozan; Durna Corum, Duygu; Corum, Orhan; Sakin, Fatih; Uney, Kamil (Wiley, 2021)
AbstractThe pharmacokinetics and bioavailability of tolfenamic acid were determined in geese (Anser cygnoides) following intravenous (IV), intramuscular (IM), subcutaneous (SC), and oral administrations at 2 mg/kg dose. In this study, eight healthy geese (3.5 ± 0.5 kg) were used. The study was performed in four periods according to a crossover design with a 15‐day washout period between two administrations. The plasma concentrations of tolfenamic acid were analyzed using HPLC‐UV, and pharmacokinetic parameters were calculated by noncompartmental analysis. The elimination half‐life was 1.73, 2.51, 2.34, and 2.31 hr for IV, IM, SC, and oral routes, respectively. The volume of distribution at steady state and total clearance after IV administration were 0.25 L/kg and 0.16 L hr−1 kg−1, respectively. The peak plasma concentrations of tolfenamic acid after IM, SC, and oral administrations were 4.89, 2.94, and 2.92 μg/ml at 0.25, 0.75, and 1 hr, respectively. The bioavailability was 87.91, 77.87, and 76.03% for the IM, SC, and oral routes, respectively. Tolfenamic acid, which exhibits the good bioavailability and plasma concentration following IM, SC, and oral administrations at 2 mg/kg dose, may be useful in the treatment of inflammatory disease conditions in geese.
Keywords: Area Under Curve; Geese; Injections, Intravenous; Animals; Biological Availability; ortho-Aminobenzoates; Injections, Intramuscular; Half-Life